Polyoxometalate–Polymer Composites with Distinct Compositions and Structures as High-Performance Solid Electrolytes - Takeru Ito (Inorganics)
Solid electrolytes, including polymer electrolytes, are a promising option for improving the performance of environmentally friendly batteries such as rechargeable lithium-ion batteries or fuel cells. Hydrogen–oxygen fuel cells producing only water under power generation are attracting widespread attention, and they need proton conductors as electrolytes. Fluoropolymer electrolytes such as Nafion® have been utilized for hydrogen–oxygen fuel cells below 100 °C; however, they are not applicable over the working temperature. Therefore, other types of polymer electrolytes are demanded for hydrogen–oxygen fuel cells. Polyoxometalate (POM) inorganic clusters are known as proton conductors and are utilized to prepare POM–polymer composites for solid electrolyte application. In such POM–polymer composites, distinct compositions and structures are significant for improving the performance of proton conductivity. Recently, POM–polymer composites with distinct compositions and structures have been synthesized to obtain high proton conductivity. The key factor is to use single-crystalline compounds. Here, several examples are overviewed by classifying them into three categories: (i) single-crystalline POM–polymer composites, (ii) organically modified POM (org-POM) polymers, and (iii) POM hybrid polymers using polymerizable cations. The application of proton-conductive solid electrolytes is focused on.